Impacts of the triple global crisis on growth and poverty in Yemen - Breisinger, Clemens; Collion, Marie-Helen; Diao, Xinshen; Rondot, Pierre (International Food Policy Research Institute, 2010)
Yemen is an oil-exporting and food-importing country on the Arabian Peninsula with persistently high levels of poverty. The impacts of the food, fuel, and financial global crises are likely to further complicate preexisting conditions of internal conflicts, decreasing oil revenues, and governance failure. The latest official growth numbers date back to precrisis levels; new estimates are subject to much debate; and the current state of poverty in Yemen remains unclear. In this paper, a consistent economic framework is presented to help close this information gap and to better understand growth and poverty dynamics during crises. Results show that economic growth in Yemen accelerated during the food and fuel crises in 2008 because oil-driven growth dominated the negative growth impacts of the food crisis. However, this oil-driven growth has not been pro-poor; in fact, poverty in both rural and urban areas rises sharply in 2008. The financial crisis in 2009 impacts Yemen mainly through the drop in oil prices and a reduction in remittances and thereby sharply slows growth, including agricultural growth. This growth decline hits households hard and compounds the poverty effects of the food crisis. Model results indicate that poverty has increased to 42.8 percent in 2009, an increase of 8 percentage points from 2005-2006, when it was 34.8 percent. Poverty continues to be much higher in rural areas, where almost half of all people lived in poverty in 2009, compared with 29.9 percent in urban areas. These estimates can be considered conservative because we do not account for conflicts and natural disasters that recently hit the country.